Band dispersion and optical gain calculations of staggered type GaAs0.4Sb0·6/In0.7Ga0.3As/GaAs0.4Sb0.6 nano-heterostructure under electric field and [100] strain. (February 2021) - Riyaj, Md; Vijay, J.P.; Khan, A.M.; Kattayat, Sandhya; Kaya, Savaş; Ahmad, M. Ayaz; Kumar, Shalendra; Alvi, P.A.; Rathi, Amit
Abstract: In this paper, the numerical calculations for the band dispersion in GaAs0.4 Sb0·6 /In0.7 Ga0.3 As/GaAs0.4 Sb0.6 staggered nano–scale heterostructure have been carried out for different values of the external electric field (0–200 kV/cm) by solving the 6 × 6 k. p Hamiltonian. In addition, the optical matrix elements have been calculated and their behaviors have been predicted for different values of field, strains and temperature. For the different values of charge carrier's injection, different field strengths and different strains along [100], the optical gain within TE (Transverse Electric) and TM (Transverse Magnetic) modes have been simulated. The maximum optical gain is achieved 16170/cm at 2000 nm at room temperature without electric field; whereas under the external electric field of 60 kV/cm at room temperature the optical gain was found to be reduced up to 11807/cm at 1955 nm. Further, with the external strain of 8 GPa, the optical gain was found to be 13965/cm at 2079 nm. Moreover, the optical gain was found to shift towards lower values with red shift in wavelength at room temperature within TE and TM modes with increasing external strain along [100] direction. On behalf of the outcomes of the simulation, the modeled heterostructure can be utilized in the design of tunable laser diode operating in MIR (mid infrared region) region. Highlights: Design of staggered type W-shaped heterostructure. Band structure and band dispersion study with and without electric field. Tunable gain characteristics with variation in temperature, uniaxial strain and electric field. Significant improvement in gain with red shift due to increase in carrier density. Employable in designing new high power IR-LEDs and modern tunable laser diodes.